2021
DOI: 10.18203/issn.2455-4510.intjresorthop20214962
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, clinico-pathological features and management pattern of primary bone tumors in a tertiary care hospital of South India

Abstract: <p><strong>Background</strong>: Primary bone tumors are very rare tumors. The true incidence of bone tumors is not well established and is under reported due to rarity and lack of accurate registries. Hence it is essential to study about the demographic, clinico-pathological features and the pattern of surgical management of bone tumors. The aim of this study is to analyze the demographic and clinico-pathological features of primary bone tumors that were managed by surgery.</p><p>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…In our own institutional experience of 15 years published in 2016, only 17% of the patients who had undergone CMP reconstructions had upper extremity tumors. 5 In the present study 40% (8) belonged to age 10-20 years, which is in accordance with literature where the malignant bone tumors like osteosarcoma peak in this age group. But if we look at the overall histopathological characteristics of patients in our study, GCT and fibromatosis took lead at 63%.…”
Section: Case Seriessupporting
confidence: 92%
See 1 more Smart Citation
“…In our own institutional experience of 15 years published in 2016, only 17% of the patients who had undergone CMP reconstructions had upper extremity tumors. 5 In the present study 40% (8) belonged to age 10-20 years, which is in accordance with literature where the malignant bone tumors like osteosarcoma peak in this age group. But if we look at the overall histopathological characteristics of patients in our study, GCT and fibromatosis took lead at 63%.…”
Section: Case Seriessupporting
confidence: 92%
“…In our own demographic data published in 2022, we noticed that 50% of upper extremity tumors turned out to be giant cell tumors. 5 Among the upper extremity tumors in our study humerus was involved in 55% (11) cases followed by radius (6) and ulna (3). Similar data was published in an epidemiological survey conducted in 2015 by Marko et al where humerus (11%) was found to be most affected followed by radius and ulna (4%).…”
Section: Case Seriessupporting
confidence: 87%